Discutindo a relação: analisando as conexões entre executivo e legislativo no estado da Paraíba (2003-2018) - Oliveira, Joseane de Azevedo (2020)
This dissertation analyzes the relationship between Executive and Legislative in the State of Paraíba, with regard to legislative production in the period from 2003 to 2018, in order to verify the supposed imposition of legislative agenda by the Executive, in addition to examining the position of the Legislative before the governor's claims. The State Constitution of Paraíba reproduces several requirements of the Federal Constitution, some of which enable the Chief Executive to act actively in legislative production. Among them, the exclusive role of legislative initiative stands out, the power to present a draft constitutional amendment, a complementary, ordinary and delegated law, in addition to the power to veto and issue provisional measures, the latter being a specific prerogative the state of Paraíba and only five other states. The research analyzed the legislative behavior of the Chief Executive and the relationship with the state parliament, in order to verify if there is an effective proactivity of the state governor in the legislative production, providing an imposition of agenda by the Executive. For the development of this research, files, minutes and data available in the Legislative Process Support System (LPSS), Legislative Diaries and specific bibliography on the topic will be used. According to the examination of the data obtained, it appears that the state executive makes use of the legislative instruments at its disposal, however it did not impose its agenda. The legislature presented itself as a body that approved the governor's claims and acted discreetly in the lawful function.